Wage-Earning Slaves COARTACION IN NINETEENTH-CENTURY CUBA Introduction - Varella, Claudia; Barcia, Manuel (University Press of Florida, 2022)
In 1845, Mark Twain was ten years old, and the society he knew in Missouri was slave-based, as the epigraph at the beginning of this book shows. Much the same was true of Cuba, a European colony at that time—Spain’s most important. But Spain’s role in slavery does not tend to be remembered as much as that of other countries. For example, in Professor Henry Louis Gates Jr.’s interview with Steve McQueen, director of the Oscar-winning movie 12 Years a Slave, McQueen failed to mention Spain when he suggested that the United States, England, Holland, France, and Portugal should...
Keywords: wage-earning slaves; Cuba; nineteenth-century; WOS(2)